If you're seeing this message, it means we're having trouble loading external resources on our website.

If you're behind a web filter, please make sure that the domains *.kastatic.org and *.kasandbox.org are unblocked.

### Course: Integrated math 2>Unit 3

Lesson 8: Strategizing to solve quadratic equations

# Strategy in solving quadratic equations

Based on the initial form of a quadratic equation, we can determine which solution methods are and aren't appropriate. Created by Sal Khan.

## Want to join the conversation?

• Completing The Square seems much faster and easier then plugging numbers into the Quadratic Equation.
When should we use the Quadratic Equation over Completing The Square? or are both valid and it's just personal preference?
• I would argue against what RN said and say completing the square is more useful, perhaps not easier though. completing the square gets you vertex form, which would allow you to more clearly graph the function.
• At ,(or really at ) can't we just say that (x+3) = -1? Sal says that it wouldn't work to say that (x+3) = 0 because the equation is (x+3)(x+1) = -1, and just jumping to x = -3 wouldn't work because that only works for x+3 = 0. But couldn't we just say that x = -4, because x+3=-1 = -4+3=-1?

So we just say that x = -4 or x = -2 instead of x = -3 or x = -1?

Does this make sense?
• It won't work because if x=-4, then it will be (4+3)(4+1)=-1, and 7*5 is not -1. The easiest way is to use the 0 property when factoring, because 0 times anything is 0. If not, there's going to me lots of guessing and error.

Hope this helps!
• It seems like completing the square takes up much less time. At what points do we use completing the square or do we use the quadratic formula
• Is there a specific way to tell which method to use? or is it a guess and check?
• I do not get it
• so for x^2+5x-3=-2+5x I first cancel the 5s, and then I work my way to the answer being x=±√1. Is that correct?
(1 vote)
• Yes, and the square root of 1 is just 1, so you can simply say x = 1 or -1. Hope this helps.
• At about , why can't you take x^2=-4x -4, and take the square root for

x=+-2x+-2

And then add or subtract the 2x from the right side to make either

3x=+-2 (and divide both sides by 3)
or
-1x=+-2
?

Thanks!
• because the √(4x-4) cannot be simplified except to take out a 4 to get 2√(x-1). All you did was divide it by 2, not take the square root
(1 vote)
• How is it that (x + 1)(x - 1) = 8 multiplies to x^2 - 1 = 8 instead of (x - 1)^2 = 8?